Frequency of positive antiphospholipid antibodies in pregnant women with SARS-CoV-2 infection and impact on pregnancy outcome: A single-center prospective study on 151 pregnancies - Gozzoli, Giorgia Ingrid; Piovani, Elda; Negri, Beatrice; Mascherpa, Margaret; Orabona, Rossana; Zanardini, Cristina; Zatti, Sonia; Piantoni, Silvia; Lazzaroni, Maria Grazia; Tomasi, Cesare; Prefumo, Federico; Sartori, Enrico; et al. (Frontiers in Immunology, 2022)
Background: At the beginning of the SARS-CoV-2 pandemic, there was a lack of information about the infection’s impact on pregnancy and capability to induce de novo autoantibodies. It soon became clear that thrombosis was a manifestation of COVID-19, therefore the possible contribution of de novo antiphospholipid antibodies (aPL) raised research interest. We aimed at screening SARS-CoV-2 positive pregnant patients for aPL. Methods: The study included consecutive pregnant women who were hospitalized in our Obstetric Department between March 2020 and July 2021 for either a symptomatic SARS-CoV-2 infection or for other reasons (obstetric complications, labour, delivery) and found positive at the admission nasopharyngeal swab. All these women underwent the search for aPL by means of Lupus Anticoagulant (LA), IgG/IgM anti-cardiolipin (aCL), IgG/IgM anti-beta2glycoprotein I (aB2GPI). Data about comorbidities, obstetric and neonatal complications were collected. Results: 151 women were included. Sixteen (11%) were positive for aPL, mostly at low titre. Pneumonia was diagnosed in 20 women (5 with positive aPL) and 5 required ICU admission (2 with positive aPL). Obstetric complications occurred in 10/16 (63%) aPL positive and in 36/135 (27%) negative patients. The occurrence of HELLP syndrome and preeclampsia was significantly associated with positive aPL (p=0,004). One case of maternal thrombosis occurred in an aPL negative woman. aPL positivity was checked after at least 12 weeks in 7/16 women (44%): 3 had become negative; 2 were still positive (1 IgG aB2GPI + IgG aCL; 1 IgM aB2GPI); 1 remained positive for IgG aCL but became negative for aB2GPI; 1 became negative for LA but displayed a new positivity for IgG aCL at high titre. Conclusions: The frequency of positive aPL in pregnant women with SARS-CoV-2 infection was low in our cohort and similar to the one described in the general obstetric population. aPL mostly presented as single positive, low titre, transient antibodies. The rate of obstetric complications was higher in aPL positive women as compared to negative ones, particularly hypertensive disorders. Causality cannot be excluded; however, other risk factors, including a full-blown picture of COVID-19, may have elicited the pathogenic potential of aPL and contributed themselves to the development of complications.